2019
DOI: 10.1097/md.0000000000015354
|View full text |Cite
|
Sign up to set email alerts
|

Post-debulking circulating tumor cell as a poor prognostic marker in advanced stage ovarian cancer

Abstract: Circulating tumor cells (CTCs) have received enormous attention as a novel biomarker in various malignant diseases. We investigated the clinical association between the presence of perioperative CTCs and survival outcomes in women with ovarian cancer. In a total of 30 women who were scheduled to undergo a surgical treatment for ovarian cancer, peripheral blood samples were obtained before and after surgery. CTCs were isolated and counted using the optimized tapered-slit filter (TSF) platform. The association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…Pear et al reported that serial measurements using CAM+ selection of CTCs could predict therapeutic responsiveness in 31 patients with ovarian cancer who received standard paclitaxel plus carboplatin therapy [11]. Kim et al found that the positive detection of postoperative CTCs using the tapered-slit filter platform was associated with inferior PFS rates in 39 patients with stage III/IV ovarian cancer (18.8% vs. 57.1%, p = 0.077) [41]. We used size-based isolation first to achieve high throughput, label-free, high-yield CTCs isolation and then used the gold standard enumeration by immunostaining with EpCAM/CK+ to define CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Pear et al reported that serial measurements using CAM+ selection of CTCs could predict therapeutic responsiveness in 31 patients with ovarian cancer who received standard paclitaxel plus carboplatin therapy [11]. Kim et al found that the positive detection of postoperative CTCs using the tapered-slit filter platform was associated with inferior PFS rates in 39 patients with stage III/IV ovarian cancer (18.8% vs. 57.1%, p = 0.077) [41]. We used size-based isolation first to achieve high throughput, label-free, high-yield CTCs isolation and then used the gold standard enumeration by immunostaining with EpCAM/CK+ to define CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Pear et al revealed that serial measurements using CAM + selection of CTCs could predict therapeutic responsiveness in 31 patients with ovarian cancer who received standard taxol plus carboplatin therapy [11]. Kim et al found that the positive detection of postoperative CTCs using the tapered-slit filter platform was associated with inferior PFS rates in 39 patients with stage III/IV ovarian cancer (18.8% vs. 57.1%, p = 0.077) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid biopsy utilizes circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), circulating cell-free microRNAs, and circulating exosomes to diagnose and monitor cancer. CTCs are more commonly found in advanced stage (III and IV) than early stage ovarian cancer [ 89 ]. They are released from primary, metastatic or recurrent ovarian cancers and can be identified in the peripheral blood [ 90 ].…”
Section: Liquid Biopsymentioning
confidence: 99%